Service Quality and Work Environment on Nurse Job Satisfaction: Work Engagement as Mediation - Alfiqul Rahmatia Idaman (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Putra Indonesia YPTK, 2023)
This study aims to determine the influence quality service and environment work to satisfaction nurse work with employment association variable intervening to the nurses at the hospital of dr. Reksodiwiryo Padang. The method used is Structural Equation Modeling (SEM) analysis using the partial least squares (PLS) program. By circulating the questionnaire as many as 60 respondents. The research results showed a positive and significant effect of service quality and work environment on nurse job satisfaction with work engagement as an intervening variable for nurses. Based on the analysis of the data, the results of the t test found thatt-table value of 2.518 P-Value value of 0.012 thus, there is a significant influence of service quality on job satisfaction through work engagement. t-table value 3.611 P-Value 0.00 thus, there is a significant effect of the work environment on job satisfaction through work engagement. this show that exists influence positive between quality service and environment work on satisfaction Work nurse with attachment Work as intervening variables in nurses at hospital dr. Reksodiwiryo Padang.